Pengaruh Brand Association dan Nutrition Label Terhadap Keputusan Pembelian Indomilk Di Kabupaten Gianyar Efek Mediasi Family Orientation - Handayani, Made Mulia; Amrita, Nyoman Dwika Ayu; Ari Santi, Dewa Ayu Kristian (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2025)
The increasingly rapid economic development has caused a lot of competition in various areas of life, as can be seen from the increasing level of competition between domestic companies and international companies. One of the competitions in the food business world is liquid milk products. The milk industry has the potential to grow in Indonesia. The purpose of this study was to determine the effect of brand association, nutrition label, and family orientation on purchasing decisions. This study uses a quantitative method. The data used is primary data that will be obtained from distributing questionnaires. The number of samples used in this study was 70 respondents. The data collection technique used was a questionnaire. The analysis technique used SmartPLS 4.1.0.3. The results of this study are that brand association has a positive and significant effect on family orientation. Brand association has a positive and significant effect on purchasing decisions. Family orientation has a positive and significant effect on purchasing decisions. Nutrition label has a positive and significant effect on family orientation. Nutrition label has a positive and significant effect on purchasing decisions. Brand association mediated by family orientation has a positive and significant effect on purchasing decisions. Nutrition label mediated by family orientation has a positive and significant effect on purchasing decisions.